Unlocking voices: The impact of Canva digital storytelling on primary ESL learners’ speaking achievement - Frecylla May Gidor; Noraini Said; Anna Lynn Abu Bakar (Global Academic Excellence, 2025)
In today's global workforce, effective speaking skills are essential for communication and professional success, making it critical to foster oral proficiency from an early age. The rapid advancement of technology has paved the way for Digital Storytelling (DST) as an innovative method to develop speaking skills by integrating multimedia that support the development of speaking competence. This study investigates the impact of Canva Digital Storytelling (DST) on enhancing speaking achievement among Malaysian primary ESL learners. A quasi-experimental design was employed involving 60 Year 5 pupils from suburban schools, divided into an experimental group using Canva DST and a control group following traditional instruction. Data collected via pre- and post-tests were analysed using paired t-tests. The findings indicated significant improvements in the experimental group. While promising, the study recommends further exploration using longitudinal and mixed method approaches as well as on different socio-cultural backgrounds to deepen the pedagogical understanding and scalability of DST.